THE EASTERN HIMALAYAN SYNTAXIS: MAJOR TECTONIC DOMAINS, OPHIOLITIC MÉLANGES AND GEOLOGIC EVOLUTION - Quanru G.; Guitang P.; Zheng L.; Chen Z.; Sun Z.; Li S.; Lou X.; Fu H.; Fisher R.D.; Ou C.; Dong H.; Wang X. (My University, 2006)
Geologic mapping in the eastern Himalayan syntaxis confirmed the three regional tectonic elements outlined by previous geologic workers. Our studies, however, show that the Indus-Yarlung Tsangpo suture (IYS) is a continuous mélange zone that forms an inverted U in map view around the Namche Barwa antiform. The Namche Barwa and Nyainqentanglha crystalline complexes lie below and above the IYS suture, respectively, and both were parts of the northern Indian plate basement rocks with petrologically and geochronologically correlative protoliths. Both units were deformed, metamorphosed and intruded at the end of the Proterozoic. The Zhibai Formation, the lower part of the Namche Barwa Group, extends along the northwest slope of the Himalaya, and is mainly composed of highly deformed aluminous felsic gneiss containing sporadic boudins of high-pressure granulite in the Namche Barwa antiform. The upper part of the Namche Barwa Group includes a calcareous rock assemblage characteristized by marble and diopside-bearing calcsilicate rocks interlayed with felsic gneiss. Petrochemical studies show that the IYS contains lenses of oceanic crustal rocks originated from fore-arc trench, island arc, and back-arc basin environments, which implies they were derived from a SSZ-type (supra-subduction zone) ophiolite. Our field mapping identifies the Jiali-Parlung Tsangpo remnant suture (JPS) that lies north of the Namche Barwa antiform as a possible branch of the Neo-Tethyan oceanic realm. Subduction of the Mesozoic Neo-Tethyan oceanic plate resulted in both Mesozoic and Cenozoic granite intrusions in the northwest-trending Gangdise magmatic belt along the southern edge of Asia. Uplift and exhumation have been the most recent dominant tectonic processes in the late Cenozoic for the High Himalayan crystalline rocks (Namche Barwa Group) in the core of the Namche Barwa antiform. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой